Expression of MUS81 Mediates the Sensitivity of Castration-Resistant Prostate Cancer to Olaparib. (21st July 2022) - Gong, Lifeng; Tang, Yu; Jiang, Li; Tang, Wei; Luo, Shengjun
Abstract : This project attempts to clarify the expression of MUS81 in castration-resistant prostate cancer (CRPC) and the effect on drug sensitivity to Olaparib. We collected clinical surgical samples of patients who were suffering from benign prostatic hyperplasia (BPH), common prostate cancer (PCa), and castration-resistant prostate cancer (CRPC) and detected the expression of MUS81 in healthy prostate epithelial cells, PCa cells, and androgen-independent PCa cells. We subsequently performed CCK-8 assays, flow cytometry, and Transwell invasion and migration assay to determine the proliferation, apoptosis, invasion, and metastasis abilities of transfected CRPC cells as well as drug toxicity of Olaparib to CRPC cells. The expression of MUS81 indicated marked upregulation in PCa and CRPC tissues, compared with the level of MUS81 in BPH tissues. MUS81 silencing inhibited the proliferation of CRPC cells and promoted their sensitivity to Olaparib. MUS81 silencing in CRPC cells remarkably accelerated cell apoptosis and greatly inhibited cell invasion and metastasis after Olaparib administration. MUS81 silencing in CRPC cells has significantly enhanced the sensitivity of cells to Olaparib, which provides evidence for the prediction of Olaparib resistance in CRPC cells by the MUS81 gene and is expected to become a promising gene target in CRPC therapy.